Integral and special methods in modelling of 3D electric fields - Doležel, Ivo; Hamar, Roman; Karban, Pavel; Ulrych, Bohuš (Видавництво Національного університету «Львівська політехніка», 2003)
Computation of large electric fields in complicated 3D arrangements (especially with geometrically incommensurable subregions) by classic numerical techniques based on differential methods often fails due to lack of boundary conditions and problems with meshing. For some of these cases the paper offers integral or special approach. Particular algorithms are illustrated on two examples whose results are discussed.